Research on heart failure in Colombia 1980-2015: a systematic review (2018)
Introduction: Heart failure is one of the most prevalent diseases worldwide. In Colombia, the state of research on the subject is unknown.Objective: To describe the original publications on heart failure in Colombia.Materials and methods: Systematic review. Digital search in Embase, PubMed, LILACS and Scielo, using the MeSH terms: “heart failure”, “Colombian”, “Colombia”, “Latin America”, “developing countries”. Manual search of 58 journals identified in Publindex. Original research that evaluated adult Colombians with heart failure and published between 1980 and 2015 were included.Results: 2 684 articles were identified, of which 35 met the inclusion criteria. 30 (85.7%) were published since 2009, 30 (85.7%) were conducted in Bogotá and Medellín, 11 (31.4%) had n200, 19 (54.2%) were descriptive and 5 (14.2%) quasi-experimental. Moreover, 9 (25.7%) described general populations, 9 (25.7%) addressed the issue of self-care, 3 (8.8%) cardiac rehabilitation, 3 (8.8%) perception of the disease and 3 (8.8%) prognostic factors.Conclusions: The amount of published original research on heart failure is low, and most of them were carried out recently. Descriptive design was the most frequent, while the most frequently addressed topics were self-care and population descriptions.